1993
DOI: 10.1002/jso.2930520314
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cryosurgery with and without the bair huggers®

Abstract: Hypothermia is a significant clinical problem during hepatic cryosurgery, which at times causes the procedure to be halted until the patient's body temperature can be raised. This study examines the effects of the Bair Hugger (a warming device) on body temperature during hepatic cryosurgery. Twenty-eight cases of hepatic cryosurgery were performed without the Bair Hugger, while 44 cases included the Bair Hugger. The lowest mean temperature was significantly lower in the group without the Bair Hugger (34.2 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The heat conservation methods described above, when applied in the early stages of the operation, appear to obviate clinically significant hypothermia during cryotherapy. Similar efforts and results regarding heat conservation have also been reported by others [17,22].…”
Section: Intraoperative Anesthetic Managementsupporting
confidence: 86%
“…The heat conservation methods described above, when applied in the early stages of the operation, appear to obviate clinically significant hypothermia during cryotherapy. Similar efforts and results regarding heat conservation have also been reported by others [17,22].…”
Section: Intraoperative Anesthetic Managementsupporting
confidence: 86%
“…In randomized trials, they have been shown to prevent hypothermia in this setting [7,11]. A significant decrease in the incidence of hypothermia, as shown in this series, when a forced-air warming device is used during laparoscopic colorectal surgery has not been previously reported.…”
Section: Discussionmentioning
confidence: 64%
“…Hypothermia was a significant problem early on in our series [50]. Ten patients had significant hypothermia with core temperatures below 33.5°C.…”
Section: Resultsmentioning
confidence: 78%